The Need for Household Panel Surveys in Times of Crisis: The Case of SOEP-CoV - Simon Kühne; Martin Kroh; Stefan Liebig; Sabine Zinn (Survey Research Methods, 2020)
The spread of the novel coronavirus, SARS-CoV-2, poses major challenges for individuals and societies at large. The question now is how individuals and society are dealing with these challenges, and what health, psychological, social, and economic effects they will have to bear. Meaningful answers can only be provided using a generalizable database that contains contextual information such as family characteristics and offers a life-course perspective. We argue that these criteria are best met by household panel survey data. In this paper, we illustrate the importance of such data and show how they can aid in explaining the current and future effects of the pandemic on individuals, households, and society. Furthermore, we describe the survey design of SOEP-CoV, a supplementary telephone survey to the German Socio-Economic Panel (SOEP) study.
Keywords: 330; coronavirus; covid-19; panel survey; longitudinal data; household surveys; SOEP